Personal finance management mobile application with chatbot - Mah, Pei Tong (2022)

(untitled)
The proposed project is a personal finance application with chatbot as my final year project in UTAR for academic purposes. Traditional budgeting and planning methods have been widely used as one of the fundamental management techniques across different types of organizations. In order to let user manage their daily expenses in a more coherent and manageable way, I developed a mobile application that integrates the knowledge of Fintech to help shape the wealth management of the user. Fintech is the integration of technology into the financial service to improve the services delivery in finance. Personal Finance Management Mobile Application with Chatbots is an android based application. This application allows the user to maintain a computerized diary that will record the expenses of a user on a day-to-day basis. Users are able to track their daily, weekly, monthly or even annually expenses with a wise distribution of categories. With the help of this application, users are able to view reports on a weekly, monthly or annually basis via graphical representation to get an overview insight of their current financing status. This can help them to stay on budget as well as be in control of their financial affairs effectively. I have reviewed these five existing finance applications, Mint, YNAB, Bluecoins, DollarBird, Goodbudget before building my system. A finding that has been found is that these five finance apps have not utilised technology like Chatbot and smart reminder in their application. Therefore, some innovative components like Chatbot and reminder are added to my application to make it stand out from the crowd of competitors. The methodology used in this project is the prototyping model which the prototype will be tested and reworked until the outcome is accepted by the customer. While the technology adoption that I used to build this application is Android studio software. All the data will be stored in the Real-time firebase for CRUD response. At the same time, IBM Watson Assistant Chatbot will be integrated into my application to serve as a virtual financing agent with automation replies. To make user feel secure when using my application, users' credential information will be identified and verified by Firebase Authentication first before one can enter into the account.